2007
DOI: 10.1021/es0714484
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of Polybrominated Diphenyl Ethers in Human Umbilical Cord Serum, Paternal Serum, Maternal Serum, Placentas, and Breast Milk from Madrid Population, Spain

Abstract: Median concentration of total PBDEs in maternal serum, paternal serum, umbilical cord serum, and breast milk samples were 12, 12, 17, and 6.1 ng/g lipid weight (lw) in Vallecas and 9.7, 12, 15, and 5.5 ng/g lw in Getafe. The median value found in placentas was 1.9 ng/g lw (in Vallecas). BDE 47 was the predominant congener in serum samples (maternal, paternal, and umbilical cord), while BDE 209 was predominant in placenta and breast milk samples. BDEs 196 and 197 were detected in most of the placenta and breast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
121
8

Year Published

2010
2010
2014
2014

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 196 publications
(148 citation statements)
references
References 39 publications
19
121
8
Order By: Relevance
“…These concentrations are comparable to those reported in human milk in Nanjing (Sudaryanto et al, 2008b), Tianjin (Zhu et al, 2009b) and Guangzhou (Bi et al, 2006), suggesting that the mean level reported here may represent the background levels of lower brominated BDEs (from tri-to heptaBDEs) in Chinese human milk. Compared with the general populations in other countries (Table 2), the PBDEs concentrations in milk in this study fell within the same range as those reported in Asian countries such as Japan (Eslami et al, 2006;Inoue et al, 2006), Indonesia (Sudaryanto et al, 2008a), Korea (Haraguchi et al, 2009), and the Philippines (Malarvannan et al, 2009), and from European countries such as Norway (Thomsen et al, 2010), France (Antignac et al, 2009), Spain (Gömara et al, 2007) and Belgium (Colles et al, 2008). The concentrations found in our study were slightly lower than those in the United Kingdom (Kalantzi et al, 2004) and Australia (Toms et al, 2007), and were one order of magnitude lower than those reported in the United States (Schecter et al, 2003).…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…These concentrations are comparable to those reported in human milk in Nanjing (Sudaryanto et al, 2008b), Tianjin (Zhu et al, 2009b) and Guangzhou (Bi et al, 2006), suggesting that the mean level reported here may represent the background levels of lower brominated BDEs (from tri-to heptaBDEs) in Chinese human milk. Compared with the general populations in other countries (Table 2), the PBDEs concentrations in milk in this study fell within the same range as those reported in Asian countries such as Japan (Eslami et al, 2006;Inoue et al, 2006), Indonesia (Sudaryanto et al, 2008a), Korea (Haraguchi et al, 2009), and the Philippines (Malarvannan et al, 2009), and from European countries such as Norway (Thomsen et al, 2010), France (Antignac et al, 2009), Spain (Gömara et al, 2007) and Belgium (Colles et al, 2008). The concentrations found in our study were slightly lower than those in the United Kingdom (Kalantzi et al, 2004) and Australia (Toms et al, 2007), and were one order of magnitude lower than those reported in the United States (Schecter et al, 2003).…”
Section: Discussionsupporting
confidence: 83%
“…These results were similar to those in other studies concerning the general population (Table 2) in France (58%) (Antignac et al, 2009) and Nanjing, Eastern China (65%) (Sudaryanto et al, 2008b). Our findings were also similar to the profiles in human milk obtained from the general population in Madrid, Spain (Gömara et al, 2007), Japan , the Philippines (Malarvannan et al, 2009) and Indonesia (Sudaryanto et al, 2008a), where a relatively higher proportion of PBDEs from octa-to deca-BDEs were detected.…”
Section: Congener Profilessupporting
confidence: 92%
See 1 more Smart Citation
“…In this study, comparatively high levels of PBDEs were found in placenta, confirming that PBDEs can cross the placenta (Gomara et al 2007). The estimated daily intakes (EDI) of PBDEs by infants via breastfeeding were determined, as follows:…”
Section: Health Risk Assessment For Infantssupporting
confidence: 76%
“…Deca-BDE is the predominant BFR used in China, amounting to 30,000 metric tons in 2005 (Zou et al 2007). Other studies have confirmed the presence of BDE-209 in the human body, e.g., serum (Qu et al 2007) and hair samples (Zhao et al 2008) from e-waste workers in China and placenta and milk samples from the general population of Spain (Gomara et al 2007) 3.3 Correlations among the three types of human specimens Studies on the relationships between concentrations of PBDEs in human hair and internal tissues are, to our knowledge, not available. Significant positive correlations were found only among the three types of TZ samples, Hair (n=5) Milk (n=5) Placenta (n=5) Hair (n=3) Milk ( ND not detected *p<0.05, **p<0.01, ***p≦0.001 regarding concentrations of total PBDEs and lower-BDEs (di-to hexa-BDEs) (r=0.998 and p<0.0001 for hair and milk; r=0.995 and p<0.0001 for hair and placenta; r= 0.999 and p<0.0001 for milk and placenta).…”
Section: Congener Profiles Of Pbdesmentioning
confidence: 97%